Experience of GIC "Ionolat" using in clinic - Volkova, Olha; Ryabokon, Eugen; Tokar, Alima; Kanunik, Tetyana; Волкова, Ольга Сергіївна; Рябоконь, Євген Миколайович; Токар, Аліма Абдулкадерівна; Кануник, Тетяна Сергіївна (My University, 2018)
Alternative materials in the restoration therapy are glass-ionomer cements (GIC), which solve the problems of treatment of demineralized dental tissues. The purpose of the study: determination of the effectiveness of treatment of caries of the chewing group of teeth with the use of GIC "Ionolat". Study had showed that using of the GIC "Ionolat" in children due to its propertieshas good long-term results, it is recommended for wide clinical practice, which is especially important in modern socio-economic conditions. Альтернативними матеріалам в реставраційній терапії є склоіономерні цементи, які вирішують проблеми лікування демінералізованих зубних тканин. Мета дослідження: визначення ефективності лікування карієса жувальної групи зубів за допомогою СІЦ "Іонолат". Дослідження показало, що використання СІЦ "Іонолат" у дітей через його властивості має хороші довгострокові результати, рекомендується для широкої клінічної практики, що особливо важливо в сучасних соціально-економічних умовах.
Keywords: caries; карієс; glass-ionomer cement; стеклоіономірний цемент